The Effect of Motivation on Teacher Performance: Mediating Role of Knowledge Sharing - Iwan Sidharta (Jurnal Ekonomi, Bisnis & Entrepreneurship, 2023)
This study investigates the potential mediating impact of knowledge sharing on the relationship between motivation and teacher performance. A study uses a sample of 53 high school teachers in Bandung to investigate the mediating effect of knowledge sharing on the relationship between motivation and teacher performance. The study incorporated motivation and knowledge sharing as independent variables, while teacher performance was the dependent variable. The research commenced by assessing the credibility and consistency of the measuring tools. Subsequently, the data were examined by applying the Structural Equation Modeling-Partial Least Squares (SEM-PLS) methodology to gain insights into the intermediary function of the research variables. The study revealed that knowledge sharing serves as a mediator between motivation and teacher performance. The findings suggest that teachers' internal drive can positively impact their performance by facilitating the exchange of knowledge. The results suggest that educators possess a substantial intrinsic drive to disseminate information, positively impacting their overall efficacy. It is essential to acknowledge that additional variables that should have been analyzed in the present research could influence teacher development.